2010
DOI: 10.1073/pnas.0913495107
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of NF-κB activity and inducible nitric oxide synthase by regulatory particle non-ATPase subunit 13 (Rpn13)

Abstract: Human Rpn13, also known as adhesion regulating molecule 1 (ADRM1), was recently identified as a novel 19S proteasome capassociated protein, which recruits the deubiquitinating enzyme UCH37 to the 26S proteasome. Knockdown of Rpn13 by siRNA does not lead to global accumulation of ubiquitinated cellular proteins or changes in proteasome expression, suggesting that Rpn13 must have a specialized role in proteasome function. Thus, Rpn13 participation in protein degradation, by recruiting UCH37, is rather selective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
56
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 29 publications
1
56
0
Order By: Relevance
“…These in vitro results indicate that active chain trimming is necessary to promote proteasomal degradation of some, if not all, proteins conjugated with Lys-48-linked polyUb chain(s). Consistent with our results, inducible nitric oxide synthase and IB-␣ were recently found as physiological substrates of Uch37-mediated proteasomal degradation (16), in which IB-␣ is known to be modified with Lys-48-linked polyUb chains by the SCF ␤TrCP E3 ligase for proteasomal degradation during NFB activation (34).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…These in vitro results indicate that active chain trimming is necessary to promote proteasomal degradation of some, if not all, proteins conjugated with Lys-48-linked polyUb chain(s). Consistent with our results, inducible nitric oxide synthase and IB-␣ were recently found as physiological substrates of Uch37-mediated proteasomal degradation (16), in which IB-␣ is known to be modified with Lys-48-linked polyUb chains by the SCF ␤TrCP E3 ligase for proteasomal degradation during NFB activation (34).…”
Section: Discussionsupporting
confidence: 78%
“…In yeast cells, depletion of Ubp6 impairs degradation of some proteasomal substrates, including Ub-Pro-␤-galactosidase (9). In mammalian cells, RNAi-medi-ated knockdown of Uch37, Usp14, Adrm1 (the Uch37 activator (13)(14)(15)), or their combinations were found to impair proteasomal degradation in cells, at least for those examined substrates (10,13,16). Moreover, inhibition of the chain trimming activity abolishes efficient degradation of some Lys-48-linked polyubiquitinated proteins in in vitro reconstituted degradation assays (17).…”
mentioning
confidence: 99%
“…Several studies, performed both in vivo and in vitro, have suggested that UCH37 can suppress protein degradation (12)(13)(14). In contrast, a recent study has suggested that UCH37 may instead promote the degradation of specific proteasome substrates, thus working similarly to RPN11 (26). We know too little to resolve these seeming contradictions.…”
Section: Usp14 and Uch37: How Do They Compare?mentioning
confidence: 69%
“…Previous work demonstrated that after 20 h of macrophage activation, iNOS is polyubiquitinated and targeted for proteasomal degradation (22). In addition, the DUB UCH37 promoted degradation of ubiquitinated iNOS via the 20S proteasome (23). WP1130 is known to target several DUBs, including UCH37, in lymphoma and HEK293 cells (18).…”
Section: Discussionmentioning
confidence: 99%